Arduino-based biosensor impedance measurement - Khamis, Nurul Najwa; Za’bah, Nor Farahidah; Mansor, Ahmad Fairuzabadi; Nordin, Anis Nurashikin (IEEE, 2016)
Currently, the cell-based biosensors have to be connected to an expensive impedance analyzer in order to obtain the measurement values. In addition, the impedance analyzer is bulky and not easily portable. Therefore, in this work, a low frequency impedance analyzer is designed by generating a low frequency AC signal that is sent to the sensor in order to measure the impedance of a cell. The prototype design is able to detect the presence of water and a cell media. It consists of a biosensor which requires a low frequency AC input signal and the impedance data of the water and cell media is to be measured and displayed using an Arduino system. The design had successfully shown that the prototype is able to detect and differentiate the two different substances based on their resistance and capacitance.